Targeted lymphadenectomy for breast cancer. Execution method. Clinical case - Shakhnoza Sh. Abdulloeva; Andrey D. Kaprin; Aziz D. Zikiryakhodzhaev; Sergey P. Prokopenko; Eric K. Saribekyan; Elena A. Rasskazova; Mikhail L. Mazo; Ekaterina A. Zanozina (LLC "MEDIAFORMAT", 2023)
There is a steady trend towards de-escalation of surgical intervention in the breast cancer treatment strategy. At first, this topic concerned the de-velopment and implementation of methods of organ-preserving operations on the mammary gland itself. With the advent of the concept and the development of the sentinel lymph node biopsy technique, the problem of performing a gentle lymphadenectomy with the prevalence of the cN0 process was solved. In recent years, the most innovative technique has begun to develop, namely targeted lymphadenectomy, which allows per- forming economical interventions on the lymph pathways with the prevalence of the cN1→ypN0 process, that is, in the presence of a verified metastatic lymph node with complete clinical resorption of metastasis during neoadjuvant polychemotherapy. The article is devoted to the de- scription of the technique of performing targeted lymphadenectomy.